Effects of SiO(2) and ZnO doping on mechanical and biological properties of 3D printed TCP scaffolds - Fielding, Gary A. (2011)
OBJECTIVES: To evaluate the effects of SiO(2) (0.5 wt %) and ZnO (0.25 wt %) dopants on the mechanical and biological properties of tricalcium phosphate (TCP) scaffolds with three dimensionally (3D) interconnected pores. METHODS: Scaffolds were created with a commercial 3D printer. Post sintering phase analysis was determined by x-ray diffraction. Surface morphology of the scaffolds was examined by field emission electron microscopy. Mechanical strength was evaluated with a screw driven universal testing machine. MTT assay was used for cellular proliferation characteristics and cellular morphology was examined by field emission electron microscopy. RESULTS: Addition of dopants into TCP increased the average density of pure TCP from 90.8 ± 0.8% to 94.1 ± 1.6% and retarded the β to α phase transformation at high sintering temperatures, which resulted in up to 2.5 fold increase in compressive strength. In vitro cell-materials interaction studies, carried out using hFOB cells, confirmed that the addition of SiO(2) and ZnO to the scaffolds facilitates faster cell proliferation when compared to pure TCP scaffolds. SIGNIFICANCE: Addition of SiO(2) and ZnO dopants to the TCP scaffolds showed increased mechanical strength as well as increased cellular proliferation.